Cervical spine MRI phenotypes and prediction of pain, disability and adjacent segment degeneration/disease after ACDF. Issue 3 (28th March 2020) - Harada, Garrett K.; Tao, Youping; Louie, Philip K.; Basques, Bryce A.; Galbusera, Fabio; Niemeyer, Frank; Wilke, Hans‐Joachim; Goldberg, Edward; An, Howard S.; Samartzis, Dino
Abstract: Degenerative spine imaging findings have been extensively studied in the lumbar region and are associated with pain and adverse clinical outcomes after surgery. However, few studies have investigated the significance of these imaging "phenotypes" in the cervical spine. Patients with degenerative cervical spine pathology undergoing anterior cervical discectomy and fusion (ACDF) from 2008 to 2015 were retrospectively and prospectively assessed using preoperative MRI for disc degeneration, narrowing, and displacement, high‐intensity zones, endplate abnormalities, Modic changes, and osteophyte formation from C2‐T1. Points were assigned for these phenotypes to generate a novel Cervical Phenotype Index (CPI). Demographics were evaluated for association with phenotypes and the CPI using forward stepwise regression. Bootstrap sampling and multiple imputations assessed phenotypes and the CPI in association with patient‐reported outcomes (Neck Disability Index [NDI], Visual Analog Scale [VAS]‐neck, VAS‐arm) and adjacent segment degeneration (ASDeg) and disease (ASDz). Of 861 patients, disc displacement was the most common (99.7%), followed by osteophytes (92.0%) and endplate abnormalities (57.3%). Most findings were associated with age and were identified at similar cervical vertebral levels; at C5‐C7. Imaging phenotypes demonstrated both increased and decreased associations with adverse patient‐reported outcomes and ASDeg/Dz. However, the CPI consistently predicted worse NDI ( P = .012), VAS‐neck ( P = .007), and VAS‐arm ( P = .013) scores, in addition to higher odds of ASDeg ( P = .002) and ASDz ( P = .004). The CPI was significantly predictive of postoperative symptoms of pain/disability and ASDeg/Dz after ACDF, suggesting that the totality of degenerative findings may be more clinically relevant than individual phenotypes and that this tool may help prognosticate outcomes after surgery.